Role of C-mannosylation in the secretion of mindin - Inai, Yoko; Ueda, Kana; Matsui, In-Sook Lee; Tajiri, Michiko; Minakata, Shiho; Wada, Yoshinao; Ihara, Yoshito (Biochimica et biophysica acta. General subjects, 2020)
Mindin (spondin2), a secretory protein related to neural development and immunity, is a member of thrombospondin type I repeat (TSR) superfamily proteins, and has a unique glycosylation of C-mannosylation in its structure. However, it remains unclear whether C-mannosylation plays a functional role in the biosynthesis of mindin in cells. Protein C-mannosylation was analyzed by mass spectrometry. Mindin expression was examined by immunoblot and immunofluorescence analyses in COS-7 cells transfected with the expression vectors for wild type (mindin-WT) or C-mannosylation-defective mutant of mindin (mindin-mutF). The redox status was examined in mindin by using 4-acetoamide-4′-maleimidylstilbene-2,2′-disulfonate. When mindin cDNA was expressed in COS-7 cells, C-mannosylation of mindin was confirmed at Trp257 by mass spectrometry. In cells expressing a mindin-mutF, secretion of the mutant was significantly inhibited compared with mindin-WT. In immunofluorescence analysis, mindin-mutF was accumulated in the endoplasmic reticulum (ER), whereas mindin-WT was detected in the Golgi. In addition, mindin-mutF showed an enhanced interaction with calreticulin, an ER-resident chaperone, in cells. In cells, reduced forms were increased in mindin-mutF, compared with a mostly oxidized form of mindin-WT. In the presence of chemical chaperones such as dimethylsulfoxide or 4-phenylbutyrate, inhibited secretion of mindin-mutF was ameliorated in cells, although redox-dependent folding was not affected. C-Mannosylation of mindin facilitates its secretion especially through modulating disulfide bond formation in mindin in cells. These results suggest that C-mannosylation plays a functional role in the redox-dependent folding and transport of TSR superfamily proteins in cells. [Display omitted] •C-Mannosylation of mindin controls its secretion.•C-Mannosylation-defective mutant of mindin is accumulated in the ER.•C-Mannosylation facilitates disulfide bond formation in mindin in cells.